Perception and practices of menstruation restrictions among urban adolescent girls and women in Nepal: a cross-sectional survey - Amrita Mukherjee; Mingma Lama; Uddhav Khakurel; Alok Nath Jha; Fatima Ajose; Sanjeev Acharya; Kristina Tymes-Wilbekin; Marni Sommer; Pauline E. Jolly; Pema Lhaki; Sadeep Shrestha (BMC, 2020)
Abstract Background Menstruation, a natural biologic process is associated with restrictions and superstitious beliefs in Nepal. However, factual data on women's perspectives on menstrual practices and restrictions are scarce. This study aimed to assess socio-cultural perceptions of menstrual restrictions among urban Nepalese women in the Kathmandu valley. Methods Using a clustered random sampling, 1342 adolescent girls and women of menstruating age (≥15 years) from three urban districts in the Kathmandu valley completed a survey related to menstrual practices and restriction. This was a cross-sectional survey study using a customized program allowing pull-down, multiple choice and open-ended questions in the Nepali language. The self-administered questionnaire consisted of 13 demographic questions and 22 questions related to menstruation, menstrual hygiene, socio-cultural taboos, beliefs and practices. Univariate descriptive statistics were reported. Unadjusted associations of socio-cultural practices with ethnicity, education, four major social classes, three major religions, marital status and family type were assessed using logistic regression models. Results More than half (59%) of the participants were aged between 15- < 25 years. The majority were Hindus (84.5%), reported not praying during menstruation (83.1%) and were encouraged by their mothers (72.1%) to practice a range of menstrual restrictions. Purifying either the kitchen, bed, bedsheets or other household things on the fourth day of menstruation was reported by 66.1% of the participants, and 45.4% saw menstruation as a "bother" or "curse." There were differences among social classes, where participants of the Janajati caste, an indigenous group, were more likely to enter places of worship [OR (95%CI): 1.74 (1.06-2.86)] and pray [OR (95%CI): 1.79 (1.18-2.71)] while menstruating, compared to the Brahmins. Participants with a master's degree were more likely to pray while menstruating, compared to participants with less than a high school education [OR (95%CI): 2.83 (1.61-4.96)]. Conclusion This study throws light on existing social discriminations, deep-rooted cultural and religious superstitions among women, and gender inequalities in the urban areas of Kathmandu valley in Nepal. Targeted education and awareness are needed to make changes and balance between cultural and social practices during menstruation.